TO LIBERTY ! The Adventures of Thomas - Alexandre Dumas - Johnson, Catherine; Sanson, Rachel, (Illustrator) (London : Bloomsbury Education, 2020)
A magical collection of short stories from double Carnegie Medal winner Margaret Mahy. A wizard's house with coloured windows that look into worlds of treetops and deserts, cloud-castles and diamonds. Two riddles that, once solved, will stop Shock Forest from burning. A flute-playing bear and a boy who just wants to spread his wings and fly... These fantastical short stories will take readers on a journey; sometimes haunting, sometimes surreal but always enchanting. This collection of brilliant stories from double Carnegie Medal winner Margaret Mahy has wonderful illustrations by TBC and is perfect for children who are developing as readers. The Bloomsbury Readers series is packed with brilliant books to get children reading independently in Key Stage 2, with book-banded stories by award-winning authors like double Carnegie Medal winner Geraldine McCaughrean and Waterstones Prize winner Patrice Lawrence, covering a wide range of genres and topics. With charming illustrations and online guided reading notes written by the Centre for Literacy in Primary Education (CLPE), this series is ideal for reading both in the classroom and at home.
The house of coloured windows -- Rooms to let -- Shock Forest -- The bridge builder -- The travelling boy and the stay-at-home bird.
"Book band: Dark Red" -- Back cover.
Junior primary school age.
Keywords: Historical fiction (Children's / Teenage) -- Juvenile fiction; Adventure stories (Children's / Teenage); Readers (Primary); Short stories